Analysis of Development of Production Infrastructure in Navoi Region - Sayfulina Alfira Feratovna (Research Parks Publishers, 2022)
Today, a significant restructuring is required, namely the improvement of the production infrastructure, technology, methods of organizing production management. This article analyzes the industrial infrastructure of the Navoi region. When analyzing the industrial infrastructure of the Navoi region, data collected during a scientific study from enterprises related to industrial infrastructure facilities were used. The author used a regression model, while building regression models of processes, the author used the least squares method.